Determinants of Human Development in Indonesia: A Comparative Analysis of The Western and Eastern Regions - Puspa Rini; Mochamad Ridwan; Purmini Purmini; Lela Rospida (PT. Maju Malaqbi Makkarana, 2026)
This study examines the effects of health, education, economic, and infrastructure expenditures, economic growth, investment, and the Labor Force Participation Rate (LFPR) on the Human Development Index (HDI) in Indonesia. It also compares the determinants of HDI between Western and Eastern Indonesia. Using a quantitative approach, the study applies panel data regression with the Common Effect Model and Ordinary Least Squares method. Secondary data from 2012–2021 were obtained from Statistics Indonesia, the Ministry of Finance, and other official institutions. The results show that all independent variables simultaneously have a significant effect on HDI. Partially, education expenditure, infrastructure expenditure, and investment have positive and significant effects, while health expenditure, economic expenditure, economic growth, and LFPR are statistically insignificant. Regional analysis reveals different determinants of HDI. In Western Indonesia, education expenditure, infrastructure expenditure, economic growth, and LFPR significantly affect HDI. In Eastern Indonesia, infrastructure expenditure, investment, and LFPR are significant determinants. These findings demonstrate that regional disparities in human development are associated with differences in economic capacity, infrastructure quality, investment distribution, connectivity, and development governance. Therefore, place-based development policies are required to improve the effectiveness and equity of human development, particularly in Eastern Indonesia.